2017
DOI: 10.1080/14653125.2016.1275442
|View full text |Cite
|
Sign up to set email alerts
|

Validating the factor structure and testing measurement invariance of modified Short-Form McGill Pain Questionnaire (Ortho-SF-MPQ) for orthodontic pain assessment

Abstract: Objective To validate the factor structure of recently modified Short-Form McGill Pain Questionnaire (Ortho-SF-MPQ) to assess orthodontic pain; and to test its Measurement Invariance (MI) across gender. Methods 180 orthodontic patients were enrolled in this study. 0.016 inch Super-elastic NiTi arch wire was used in 0.022″ × 0.028″ slot pre-adjusted edgewise appliance. After initial arch wire placement, pain was assessed at T1 (24 hours), T2 (day 3), and T3 (day 7) by using the Ortho-SF-MPQ which consists of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 12 publications
1
14
0
Order By: Relevance
“…And MPI was originally developed for patients with chronic cancer [10]. Recently the SF-MPQ was adapted to measure the orthodontic pain and was named Ortho-SF-MPQ [12]. The author performed the validation (confirmatory factorial analysis) of the instrument and validity and reliability were attested in Indian patients undergoing corrective orthodontic treatment [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…And MPI was originally developed for patients with chronic cancer [10]. Recently the SF-MPQ was adapted to measure the orthodontic pain and was named Ortho-SF-MPQ [12]. The author performed the validation (confirmatory factorial analysis) of the instrument and validity and reliability were attested in Indian patients undergoing corrective orthodontic treatment [12].…”
Section: Introductionmentioning
confidence: 99%
“…Recently the SF-MPQ was adapted to measure the orthodontic pain and was named Ortho-SF-MPQ [12]. The author performed the validation (confirmatory factorial analysis) of the instrument and validity and reliability were attested in Indian patients undergoing corrective orthodontic treatment [12]. This instrument is a viable alternative for the measurement of pain, but, unlike BPI and MPI, it evaluates pain in the qualitative aspect and does not extend this evaluation to the quantitative and general aspects of individuals' lives.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding individual characteristics, the fact that women reported a greater impact of orthodontic pain is corroborated in the literature . This difference was attributed to the presence of sex hormones; however, this is speculative because these conditions were not evaluated.…”
Section: Discussionmentioning
confidence: 74%
“…Regarding age, some authors observed that adolescents report higher intensity and prevalence of pain after orthodontic appliance activation . Regarding sex, others have observed that women report higher mean pain scores . Patients’ socioeconomic stratum has also been considered to be relevant in the evaluation of pain .…”
Section: Introductionmentioning
confidence: 99%
“…The results of this study suggest that an effective ACT period has a significant effect on the quality of life of women suffering from chronic low back pain. [15,[20][21][22]. For instance, Mason et al (2008) have shown that accepting low back pain improves the quality of life of those who suffer from chronic low back pain [15].…”
Section: Discussionmentioning
confidence: 99%